Illuminating and Sniffing Out the Neuromodulatory Roles of Dopamine in the Retina and Olfactory Bulb - Korshunov, Kirill S.; Blakemore, Laura J.; Trombley, Paul Q. (Frontiers in Cellular Neuroscience, 2020)
In the central nervous system, dopamine is well-known as the neuromodulator that is involved with regulating reward, addiction, motivation, and fine motor control. Yet, decades of findings are revealing another crucial function of dopamine: modulating sensory systems. Dopamine is endogenous to subsets of neurons in the retina and olfactory bulb (OB), where it sharpens sensory processing of visual and olfactory information. For example, dopamine modulation allows the neural circuity in the retina to transition from processing dim light to daylight and the neural circuity in the OB to regulate odor discrimination and detection. Dopamine accomplishes these tasks through numerous, complex mechanisms in both neural structures. In this review, we provide an overview of the established and emerging research on these mechanisms and describe similarities and differences in dopamine expression and modulation of synaptic transmission in the retinas and OBs of various vertebrate organisms. This includes discussion of dopamine neurons’ morphologies, potential identities, and biophysical properties along with their contributions to circadian rhythms and stimulus-driven synthesis, activation, and release of dopamine. As dysregulation of some of these mechanisms may occur in patients with Parkinson’s disease, these symptoms are also discussed. The exploration and comparison of these two separate dopamine populations shows just how remarkably similar the retina and OB are, even though they are functionally distinct. It also shows that the modulatory properties of dopamine neurons are just as important to vision and olfaction as they are to motor coordination and neuropsychiatric/neurodegenerative conditions, thus, we hope this review encourages further research to elucidate these mechanisms.